The Legal Regime for Consumer Protection in Drug Administration and Control in Nigeria - N.J , Obumneme-Okafor (African Journal of Education,Science and Technology (AJEST), 2017)
The drug industry forms part of the live wire of every society and the state of health of every society largely depends on it. This is because the consumption of drugs by people affects their lives positively or otherwise depending on whether the consumed drug is of the desired quality and consumed in the right quantity and at the right time. A whole lot about the efficacy and effectiveness of drugs depends on their administration. Even if a drug is of good quality, yet if it is not well administered, it will not give the desired result. It is a notorious fact that the enforcement of the available legal framework for drug administration in Nigeria leaves much to be desired in spite of the availability of the legislations on the subject. It is thus either that the legislations are not adequate to deal with the situation or that their implementation by the appropriate authorities or institutions is the problem or both. The place of importance occupied by the state of health of the nation in its development and sustenance can hardly be over emphasized. The statutes in focus are the Poisons and Pharmacy Act, Food and Drugs Act and the National Agency for Food and Drugs Administration and Control Act. An examination of the operation of the related agencies created under or by these laws (if any) in the enforcement of the provisions of these statutes needs to be undertaken. The work will examine the problems associated with the administration of laws and the agencies and attempt proffering solutions to such problems so as to create a consumer friendly environment in drug administration in Nigeria where the consumer will consume the drugs to be healthy and not to die or have his health jeopardized or compromised.